Kebugaran Fungsional pada Lanjut Usia Laki-laki dan Perempuan - Dwi Purwantini; Ni Nyoman Wahyu Lestarina (Universitas Negeri Surabaya, 2024)
Background: Functional fitness is a concept that represents the optimal physical capacity required to continue normal daily activities, independently and without the onset of premature fatigue. The research aims to determine functional fitness in elderly people between the ages of 60-69 (young elderly) and 70-84 (older elderly). Methods: This research is to carry out a senior fitness test, namely a series of tests to assess functional fitness in the elderly. The research subjects were 31 elderly women and men, aged 60 - > 85 years. The test consists of 5 functional fitness measurements, as follows 30-Second Chair Stand Test, 30-Second Arm Curl Test, 2 minute step test, Chair Sit and Reach test and 8 Foot Up and Go Test. Results: The results of this study: Most elderly people have good leg and upper limb strength which was obtained from examination with the 30-second chair stand test (68%), and 30-second arm curl test (90%). Aerobic endurance from the two minute step test was obtained by the majority of elderly people with good results (97%), limb flexibility from the results of the chair and reach test (57%). Coordination, agility and dynamic balance obtained from the 8 foot up and go test showed that most (68%) were poor Conclusions: Elderly people at Posyandu Rosan Kemuning RW 3 Kebraon Subdistrict and Rumah SSpS Java Province showed that most of the functional fitness components (muscle strength, flexibility, aerobic endurance) were good. Coordination, agility and dynamic balance are lacking. Further research needs to be done regarding exercise or physical activity to improve functional fitness components that are lacking